O Baluarte de S. João. Repensar, Reabilitar, Inovar - Afonso Ferreira de Sousa Ramos de Abreu (2019)
The main theme is the location. The defensive wall, its contents and its surroundings. The context and the way the past and possible future influence new thoughts. The precedents and the way these will remain, despite future modernizations. This dissertation covers the proposal for a plot located inside the "Baluarte de S. João", in the city of Setúbal. This heritage site is inserted in the northeast end of the Historical Centre. Separated from the Centre by the railway, axis that seems to limit the psychology of conservation and evolution of this direction of the territory. This area, limited and defined by the stone wall, grew along with the city, by being appropriated, through time, by diverse constructions. A project that aims to recover and restore its existence was developed, by making it modern without losing the essence of its past. In this context, a study was conducted on the psychology behind working with the present, to, in some extent, define strategies of approach. The interior of the "Baluarte" is currently occupied merely for housing, with the existence of constructions along the plot for diverse purposes. The inhabitance was rethought to be lived with better quality and usefulness. Spaces were created to permit an intertwined livelihood with the exterior. The exterior was though so that it connected with the public spaces. The in-between was drawn so that the new constructions would connect with the city and cohabit with the heritage. This study is about isolated spaces and their reintegration.